Molecular cloning and characterization of partial cDNA encoding for dehydroascorbate reductase from kelampayan (neolamarckia cadamba) - Ng, Siew San (Universiti Malaysia Sarawak, UNIMAS, 2013)
Neolamarckia cadamba or locally known as Kelampayan is an evergreen and tropical forest tree. It has high commercial value for timber production and possesses several medical values, such as anthelmintic and astringent production. The intention of this study was to isolate and characterize the partial complementary DNA (cDNA) of Dehydroascorbate reductase (DHAR) gene by using RT-PCR in Kelampayan. Dehydroascorbate reductase (DHAR) is an important reducing enzyme in ascorbate-glutathione cycle. It maintains the level of ascorbate in the plants. Ascorbate (AsA) protects the plants from environmental stress.It also involved in controlling the appropriate signaling in guard cell. In this study, ribonucleic acid (RNA) of N. cadamba was extracted from fresh young leaves of Kelampayan and the purified polymerase chain reaction (PCR) product was sent for direct sequencing. Results showed that the partial cDNA of N.cadamba was successfully isolated. The sequence had high similarity when compared with DHAR in other species using BLASTn and BLASTp. The partial cDNA of DHAR gene isolated was the middle region when compared to the complete cDNA of DHAR in Populus tementosa.